La resiliencia y el empoderamiento en hombres y mujeres víctimas de violencia intrafamiliar en el municipio de Cajicá (2021)
Throughout history, violent behavior has been observed on the part of the human being, however, different categories have also been known and established within this behavior, such as intrafamily violence, which according to Camacho et al (2020) "is the action of a member of the family against any of its members in the space of family coexistence, against their will or desire. It covers verbal offenses, physical or mental harm, intimidation, sexual abuse or economic control” (p. 24).